Apparatus and method for prioritization of multiple commands in an instrumentation and control system - LANG; GLENN E (1998)
Prioritization logic determines the final command applied to a process control component from a plurality of commands generated by diverse independent control subsystems, each utilizing different hardware and software to implement a common algorithm to preclude common mode failures. In one embodiment, priority is given to commands generated by one control subsystem, such as a safety grade subsystem, over commands provided by a second, non-safety grade control subsystem. In another embodiment, equal priority is given to commands from two control subsystems. In this case, ambiguous commands from either or both subsystems are ignored, but conflicting commands produce a final command which provides a safe state.